(untitled) (Web of Teachers: Inderscience Research, 2024)
At its core, any form of theoretical cooperation, regardless of type, inherently possesses socio-psychological characteristics. By considering these socio-psychological traits during the organization and execution of cooperative efforts, desired outcomes can be achieved. Therefore, when planning collaborative activities, it is crucial to shape their content while taking into account these socio-psychological factors to ensure the expected results are met. The cooperation between higher education institutions (HEIs) and the Mahalla Institute exemplifies these socio-psychological characteristics, common to all joint activities. The article explores these features and how they are reflected in the cooperation between the Mahalla Institute and universities.